Virtual laboratories and m-learning: learning with mobile devices - Bottentuit Junior, João Batista (2007)
This paper introduces the concept and the advantages of using virtual laboratories through mobile devices. It will also be introduced some concepts related to learning objects and m-learning. We also present the virtual experience used for the virtual mobile laboratory. In the end, we indicate the ideal methodology to use these technologies when teaching chemical experiments.